DETERMINATION OF THE BIOCHEMICAL COMPOSITION OF ZOOPLANKTON PRESENT IN LAKE ZAMONBOBO (Eureka Journal of Agricultural Science & Bio-Innovation, 2026)
This article is devoted to determining the biochemical composition of zooplankton species present in Lake Zamonbobo. The study assesses the importance of zooplankton in the food chain in the lake ecosystem by analyzing their levels of lipid, protein, carbohydrate, and other important biochemical components. The results provide important information for understanding the lake's trophic level, water quality, and fishing potential. The information obtained will serve as the basis for developing strategies for the rational use and protection of the biological resources of Lake Zamonbobo.
Keywords: Lake Zamanbobo, zooplankton, biochemical composition, lipids, proteins, carbohydrates, ecosystem, trophic level, water quality.